PENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS MELALUI PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBANTUAN MACROMEDIA FLASH PADA SISWA KELAS VI SD MATERI BANGUN DATAR - SILABAN, PATRI JANSON; HASIBUAN, ASNITA (Jurnal Ilmiah Aquinas, 2020)
The problem in this research is learning rarely uses media in learning,Â Â students' mathematical understanding ability is still low in mathematics learning flat-build material, lack of learning media. This study aims to determine the relationship of the development of Macromedia Flash-assisted mathematics learning media related to flat material. This research method uses research and development (Research and Development). The 4-D device development model consists of 4 stages of development, namely Define, Design, Develop and Disseminate or adapted into a 4-D model, namely defining, designing, developing and disseminating. In the field trials the average pretest score is 68.24 while the average posttest score is 86.76. An average increase of 18.52. The minimum gain value is 0.62 while the maximum gain value is 1.00. In the test of the spread of the average pretest value is 60.33 while the average posttest score is 81.33. An average increase of 21. The minimum gain value is 0.77 while the maximum gain value is 0.83. Based on these data, the development of mathematics learning media assisted by macromedia flash has experienced a significant increase in students' mathematical understanding abilities.